BOLÍVAR ECHEVERRÍA: EL EXISTENCIALISMO DEL SIGLO XX - Anangonó Rosero, Gerson Gabriel (2019)
This study reviews the intellectual biography of the Ecuadorian philosopher Bolívar Vinicio Echeverría Andrade about existentialism; being this one of the maximum referent of the philosophy for Latin America. The project covers the approach of Echeverría with the existentialism of the twentieth century. Through the inscription of his work and thought in The Humanism of Existentialism. Through a hermeneutical methodology, which has permitted studying the historical context for the emergence of the existentialism of the twentieth century and its relevant theoretical representatives, until conceiving the perspective of Bolívar Echeverría on the existentialism raised by Sartre in his writing Existentialism is a humanism.